Incidence and differentiation of Cucumber mosaic virus (CMV) isolates in Peninsular Malaysia - Saad, Norsazilawati (2012)
A survey on the occurrence and incidence of Cucumber mosaic virus (CMV) was carried out on selected horticultural crops in Peninsular Malaysia. A total of 1293 leaf samples showing virus-like symptoms comprising of chilli (527 samples), tomato (63 samples), eggplant (183 samples), cucumber (209 samples), pineapple (161 samples), long bean (49 samples), and loofah (101 samples) were collected from the field at 35 different locations in 7 states (Selangor, Pahang, Melaka, Johor, Kelantan, Perak and Pulau Pinang) to detect the presence of CMV. The detection of CMV was done using double antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA). Based on the DAS-ELISA results, CMV was detected in 9% of the entire surveyed crops. The highest percentage of CMV incidences was found in Selangor with 48% infection, followed by Kelantan and Melaka (15%),Pahang (8%), Johor (7%), Pulau Pinang (4%), and Perak (1%). Amongst the samples collected, CMV was discovered to be the most prevalent on eggplant and chilli with 12% disease incidence each, followed by tomato (10%), cucumber (5%), long beans (4%) and pineapple and loofah (3% each). CMV-infected samples detected by DAS-ELISA were used in reversetranscription polymerase chain reaction (RT-PCR) analysis. Gene-specific primers were designed and a primer was then selected to amplify the region of coat protein (CP) gene, producing a specific band sized of approximately 600 base pair (bp). Samples used for RT-PCR included crops collected from Selangor, Pahang, Melaka, Johor, Kelantan, Perak, Pulau Pinang and with an addition of samples from Terengganu. Only crops collected from Johor (long beans, eggplant, cucumber, chilli and pineapple), Pahang (chilli, tomato, cucumber and eggplant), Terengganu (chilli, loofah and eggplant),Perak (cucumber), Pulau Pinang (chilli) and Selangor (chilli, tomato and eggplant) produced DNA bands of approximately 600 bp in size. Nucleotide sequences of the CP gene of 20 CMV isolates from tomato,eggplant, loofah, chilli and tobacco collected in Terengganu, Pahang,Penang, Perak and Selangor were confirmed as CMV. Phylogenetic analysis of the partial CP genes suggest that the local CMV isolates belong to subgroup I (S-I) and are grouped together with the subgroup IB (S-IB) strains. The results further proposed that the isolates can be arranged according to the type of crops and geographical location.